HYBRID METHOD OF THE HOUSE OF RISK AND MONTE CARLO FOR PLANNING MODELS ON THE NEW CONSTRUCTION OF PROJECT X - Simon Fuad Sonda; Mukhlis Mukhlis; Ahmadi Ahmadi (Indonesian Naval Technology College STTAL, 2022)
The series of activities which include the preparation and selection of various alternatives, as well as theirimplementation, are carried out in a way and logically so that the consequences that may occur can be predictedand anticipated. In an activity, especially a project, risks are an inseparable part. HOR method is used to identify andmeasure impact risks on project X. Monte Carlo simulation is used as a simulator in estimating the completion ofa project. The simulation results on project X are known that there are 30 potential events that occur due to 29risk agents in the project. The trajectory critical of the project happens in activity A-B-C-D-E-F-G-H-M-V-W-AG-AHAI-AJ-AK. Based on the simulation of the results Montecarlo with crystal ball software knew that with under risk so thesolution project became pessimistic with timely completion of 1.074 days or 351 late than the time already planned Keywords: Risk Management, Project Management, Forecasting, House of Risk, Monte Carlo